FIRM SPECIFIC CHARACTERISTICS AND DIVIDEND PAYOUT RATIO: AN INSIGHT OF QUOTED COMPANIES ON THE NIGERIAN STOCK EXCHANGE - Oluwaseyi Ayodele Adedipe; Sunday Azeita Okoughenu (Malete Journal of Accounting and Finance)
This study investigates the relationship between firm specific characteristics and dividend payout ratio of quoted firms in Nigeria. The population of the study consists of one hundred and sixty-nine (169) firms listed on the Nigerian Stock Exchange as at 31st December 2018 and from which a sample of one hundred and two (102) firms were selected for a period of nine (9) years spanning from 2010 to 2018 making a total of nine hundred and eighteen (918) completed observations. Data collated from secondary source were analysed on the basis of POLS, FE and RE estimates. For the purpose of consistency and efficiency, the study further carried out post estimation test which include restricted F-test and Hausman test. The estimation result of the RE indicated that inventory intensity and firm share price intensity jointly had a positive and significant relationship with dividend payout ratio. In addition, capital intensity, labour intensity and R&D intensity jointly had a negative and significantly relationship with dividend pay-out ratio. Hence, this study recommends that managers of Nigerian quoted firms should lower the amount of cash spent on capital intensity, labour intensity and R&D intensity so that the value of profitability will increase; and the same time, dividend pay-out ratio will equally increase. In addition, inventory intensity and share price intensity of the firms should be maintained so as to continue paying good dividend to the shareholders that will lead the firm to achieve the shareholders’ value maximisation objective.